2009
DOI: 10.1080/01932690903123403
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-DNA Particles for DNA Delivery: Effect of Chitosan Molecular Weight on Formation and Release Characteristics

Abstract: Novel DNA-chitosan particles were prepared based on associative phase separation and interfacial diffusion. These particles formed at water/water emulsion type interfaces were characterized with respect to several properties including stability, DNA conformational state, and entrapment and release of DNA. In particular it was found that the chitosan molecular weight is a good controlling parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The formation of the chitosan-DNA gel particles was studied using mixtures of DNA and chitosan of different molecular weight ((Low MW chitosans of ca. 50 kDa and 150 kDa, and medium MW chitosan (400 kDa) [74] .The molecular weight of the polysaccharide structure did not have a clear effect on the LC values.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The formation of the chitosan-DNA gel particles was studied using mixtures of DNA and chitosan of different molecular weight ((Low MW chitosans of ca. 50 kDa and 150 kDa, and medium MW chitosan (400 kDa) [74] .The molecular weight of the polysaccharide structure did not have a clear effect on the LC values.…”
mentioning
confidence: 94%
“…Novel chitosan-DNA gel particles have been prepared based on associative phase separation and interfacial diffusion using mixtures of DNA and chitosan of different molecular weight [74][75]. In particular it was found that the chitosan molecular weight is a good controlling parameter in the final properties of these DNA gel particles [74].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…This DNA concentration was chosen because it produces high-viscosity solutions, which makes it an appropriate system for the preparation of stable DNA gel particles. [3][4][5][6][7][8][9] Particles were prepared by dropwise addition of DNA solutions to the surfactant solutions, equilibrated at 25 or 45ºC. Because of the relatively high viscosity of the DNA solution, mixing of the two solutions is not instantaneous.…”
Section: Particle Preparationmentioning
confidence: 99%
“…By mixing solutions of DNA (either single-stranded (ssDNA) or double-stranded (dsDNA)) with solutions of different cationic agents, such as surfactants, proteins and polysaccharides, the possibility of the formation of DNA gel particles without adding any kind of cross-linker or organic solvent has been confirmed. [3][4][5][6][7][8][9] The strength of association, which is tuned by varying the structure of the cationic agent, allows control of the spatial homogeneity of the gelation process, producing either a homogeneous DNA matrix or different reservoir devices. This gives rise to various applications for the controlled encapsulation and release of ssDNA and dsDNA, with clear differences in their mechanism.…”
Section: Introductionmentioning
confidence: 99%